FINANCIAL RESTRUCTURING IN CONDITIONS OF WARTIAL LAW - VDOVICHEN, Anatolii; SHPATAKOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on the analysis of financial restructuring in times of war, specifically its significance, strategies, and challenges arising in the context of armed conflict. Key aspects such as reduced economic activity, financial pressure, and the threat of corporate bankruptcy in wartime conditions are examined. The article also identifies unresolved issues like socio-economic inequality and banking system instability. It highlights the importance of financial restructuring as a tool to overcome economic difficulties and ensure stability during a crisis conflict. The purpose of the article is to identify financial restructuring strategies in times of war, illuminate key challenges and unresolved issues in this context, and indicate possible ways to improve the effectiveness of financial reforms to ensure the stability of the economy and financial system during wartime. The relevance of researching financial restructuring in times of war for Ukraine is extremely high, given the country's complex geopolitical conditions and the challenges it faces. War, aggressive actions by neighboring states, and global instability make Ukraine's financial sector vulnerable to external shocks and economic turbulence. The significance of this topic is underscored by the necessity to develop and implement strategies aimed at ensuring the stability of the financial system, supporting economic development, and ensuring social well-being in the context of wartime conflict. Further research in this direction is a crucial step in understanding the impact of wartime on financial markets and in developing innovative strategies that will enable Ukraine to effectively adapt to challenges and maintain economic resilience in these unpredictable conditions. The analysis reveals prospects for improving financial restructuring through the adoption of innovative technologies and enhancement of regulatory mechanisms. The research provides practical recommendations for leadership and financial institutions to more effectively address financial challenges during wartime. In conclusion, the article emphasizes the importance of further research in this area and suggests possible paths for developing strategies aimed at stabilizing the financial system and ensuring economic resilience in unpredictable wartime conditions.
Keywords: financial restructuring; financial challenges; financial strategies; economic resilience; wartime; financial reforms